Clarifying the anatomy and physiology of totally anomalous systemic venous connection - Saurabh Kumar Gupta; Rajnish Juneja; Robert H Anderson; Gurpreet S Gulati; Velayoudam Devagorou (Wolters Kluwer Medknow Publications, 2017)
The description of totally anomalous systemic venous connection is limited to case reports. In this review, we seek to clarify anatomic, physiologic, and hemodynamic aspects of this extremely rare anomaly. We also present findings of two patients in whom connection of all the systemic veins was anomalous. In the first patient, with usual atrial arrangement, all systemic veins, including the coronary sinus, were connected anomalously to the morphologically left atrium. Limited left-to-right shunt across an atrial septal defect provided the only source of blood flow to the lungs. The diagnosis was established by saline contrast echocardiography and cardiac catheterization. Extreme hypoplasia of the right ventricle precluded corrective surgery, so we performed a bidirectional Glenn operation, along with atrial septectomy. The second patient had isomerism of the left atrial appendages, which creates problems in the definition in anatomic terms since the connection of the systemic veins can never be normal anatomically when both atriums possess a morphologically left appendage. Our patient, nonetheless, had all the systemic and pulmonary veins, connected to the left-sided atrial chamber which then connected to the left ventricle, thus producing hemodynamics of totally anomalous systemic venous connection. We propose an algorithm for evaluation of this hemodynamic combination and discuss management options. We also intend to clarify the potential differences between connection and drainage, with particular attention to the arrangement of atrial appendages. Even though the hemodynamics may be comparable, in anatomic terms, both systemic and pulmonary venoatrial connection will always be anomalous with isomeric atrial appendages.